2017
DOI: 10.1155/2017/4687154
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Control of Uropathogenic Microorganisms with the Ethanolic Extract from the Leaves of Cochlospermum regium (Schrank) Pilger

Abstract: The roots of Cochlospermum regium, popularly known as “algodãozinho-do-cerrado,” are used for the treatment of genitourinary infections. However, the removal of their subterranean structures results in the death of the plant, and the use of the leaves becomes a viable alternative. Therefore, the antimicrobial activity of Cochlospermum regium leaf's ethanolic extract and its action on the biofilm formation of microorganisms associated with urinary infection were evaluated. The total phenolic compounds, flavoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
5
0
4
Order By: Relevance
“…Considering our previous findings on the antimicrobial activity of ECR against other pathogenic microorganisms [ 22 ], we believe that this extract is even more promising for the treatment of hospital and domestic surfaces. This is because, considering its proven action against E. coli , Candida tropicalis , and now Cryptococcus (specifically the C. gattii complex of resistant species), ECR could be used to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Considering our previous findings on the antimicrobial activity of ECR against other pathogenic microorganisms [ 22 ], we believe that this extract is even more promising for the treatment of hospital and domestic surfaces. This is because, considering its proven action against E. coli , Candida tropicalis , and now Cryptococcus (specifically the C. gattii complex of resistant species), ECR could be used to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 95%
“…This is because, considering its proven action against E. coli , Candida tropicalis , and now Cryptococcus (specifically the C. gattii complex of resistant species), ECR could be used to prevent biofilm formation. It is important to highlight that our previous study showed that ECR is innocuous for animal cells (92% cell viability for VERO lines) and did not show mutagenic potential in an Ames assay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os pesquisadores observaram também bons resultados fungicidas contra Candida krusei, Candida glabrata, Candida tropicalis e Candida albicans. Leme et al (2017), avaliaram in vitro a atividade contra microrganismos uropatogênicos a partir do extrato etanólico das folhas de C. regium. Uma baixa atividade de inibição foi observado para E. coli e discreta para C. tropicais, demonstrando que o extrato foliar pode ser utilizado individual ou em conjunto com outros princípios ativos para o uso como antibiótico e antifúngico.…”
Section: Atividades Biológicasunclassified